Performance Evaluation of Firman FPG1500ECII Generator Set after Maintenance and Overhaul with Various Gasoline Fuels - Herlin Sumarna; Toni Okviyanto; Tri Satya Ramadhoni; Agis Fika Wulandari; Indra Syahputra; Stevan Juliandro Aruan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Generator sets are widely used as a backup power source for household and small industrial applications. The reliability of a generator set is strongly influenced by the condition of its engine components and the maintenance quality. This study aims to evaluate the performance of a Firman FPG1500ECII generator set after maintenance and overhaul using three different gasoline fuels, namely Pertalite, Pertamax 92, and Pertamax Turbo. The research stages consisted of visual inspection, failure identification, maintenance and overhaul processes, and performance testing under a constant load of 540 W. The performance parameters investigated included electrical power output, fuel mass flow rate, Specific Fuel Consumption (SFC), electrical efficiency, and Brake Thermal Efficiency (BTE). Initial inspection results revealed failures in the piston ring, connecting rod bearing, and main bearing, as well as carbon deposits in the combustion chamber and valve system, causing the generator set to fail completely. After maintenance and overhaul, the generator set was successfully restored and subjected to performance testing. The results indicated that fuel type significantly affected generator performance. Pertamax Turbo exhibited the best performance with a fuel mass flow rate of 0.2751 kg/h, SFC of 1.557 kg/kWh, electrical efficiency of 5.18%, and BTE of 76.55%. In contrast, Pertalite showed the highest fuel consumption with a fuel mass flow rate of 0.4155 kg/h, SFC of 2.405 kg/kWh, electrical efficiency of 3.36%, and BTE of 50.68%. The findings demonstrate that maintenance and overhaul successfully restored the operational performance of the generator set, while higher-octane fuels improved combustion efficiency and overall generator performance after maintenance. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action